2018
DOI: 10.1039/c7ra12775h
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of diethylnitrosamine (DEN)-induced hepatocellular carcinogenesis in animal modelsviaknockdown oxidative stress and proinflammatory markers byMadhuca longifoliaembedded silver nanoparticles

Abstract: In hepatocellular carcinoma (HCC), primary liver cancer is primarily responsible for inflammation-related cancer as more than 90% of HCCs emerge with regard to hepatic damage and inflammation. Tenacious inflammation is known to advance and intensify liver tumours. Nanomaterials, for example, silver nanoparticles synthesized from plant-derived materials have shown great outcomes in reducing the precancerous nodules and have anticancer properties. The aim of the present investigation was to biosynthesize, charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 52 publications
1
29
0
Order By: Relevance
“…The mean body weight of HCC group (group III) was less than the other three groups with no stastistically significant reduction that might be related to the toxic effect of CCL4 and DEN and the decrease of the appetite. Similar studies related to HCC reported body weight reduction and tissue destruction (Singh et al, 2018;Badr El-Din et al, 2020) as compared to the control group.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The mean body weight of HCC group (group III) was less than the other three groups with no stastistically significant reduction that might be related to the toxic effect of CCL4 and DEN and the decrease of the appetite. Similar studies related to HCC reported body weight reduction and tissue destruction (Singh et al, 2018;Badr El-Din et al, 2020) as compared to the control group.…”
Section: Discussionsupporting
confidence: 76%
“…The mean wet liver weight of rats with HCC (group III) and HCC-T. spiralis (group IV) was increased with the time of the experiment with higher increase in group III on the 40 th day from the onset of tumor formation. This increase might be explained by the effect of DEN on the liver as mentioned by JO et al, (2016) and Singh et al, (2018) who stated that treatment with DEN to induce HCC caused increasing in the liver weight. Meanwhile, the reduced liver weight in group IV as compared to group III suggested that the enlargement of the liver caused by DEN might be diminished by effect of T. spiralis infection.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Group 1 Normal control untreated rats fed with standard diet and administered orally with 0.5 mL normal saline by gastric intubation. Group 2 Rats were injected with DEN to induce hepatocarcinogenesis by providing a single dose of intraperitoneal injection (i.p) of DEN (200 mg/kg BW) on the first day of the experiment [27].…”
Section: Experimental Protocolmentioning
confidence: 99%
“…DEN is used to induce precancerous and cancerous lesions. It is metabolically activated by the liver cytochrome cytochrome P450 (CYP450) system, followed by induced DNA damage and oxidative stress in hepatocytes during cancer initiation[ 18 ]. The drawback of this model is the duration required for appropriate tumor development[ 19 ].…”
Section: Discussionmentioning
confidence: 99%